ANALYSIS OF VILLAGE APPARATUS COMPETENCE AT THE LINAWAN 1 VILLAGE OFFICE, PINOLOSIAN DISTRICT, SOUTH BOLAANG MONGONDOW REGENCY - Ramla Bajeneti; Djamila Podungge; Desi Putri Dama (Jurnal Ilmu Manajemen dan Bisnis, 2025)
This study aims to determine the level of understanding of village apparatus regarding their primary duties and functions, as well as to assess their ability to use Information and Communication Technology (ICT). This research uses a qualitative descriptive research type. This research employs a method that aims to describe and interpret the object in accordance with field reality. The use of the explanatory method seeks to create, systematically and factually, descriptions, illustrations, or depictions of the facts, characteristics, and relationships among the phenomena being investigated. The results are expected to serve as a basis for planning to improve the capabilities of village apparatus to realize more professional, efficient, and flexible village governance in line with development.